Creatinine clearance levels are associated with the incidence of preeclampsia - Sanusi, Jesslyn M; Tendean, Hermie M. M.; Kaeng, Juneke J. (Indonesian Socety of Obstetrics and Gynecology, 2018)
Abstract Objective: Determine thecorrelation between creatinine clearance relationship with preeclampsia incidence. Method: Cross sectional research. Result: Creatinine clearance examination conducted on 60 sample of pregnant women > 20 weeks,30 normotensive samples and 30 preeclampsia samples. The obtained data analyzed using SPSS software version 22.0 and discussed using the existing literature theory. Creatinine clearance average level in normotensive pregnancy 124.650 ± 14.3699ml/minutes/1,73m2and preeclampsia 74.003 ± 23.169ml/minutes/1,73m2. After Mann-Whitney statistical test obtained p value = 0,000. From ROC curve analysis for creatinine clearance obtained sensitivityvalue 100% and specificity 99,53%. Conclusion:There is a significant correlation between the creatinine clearance levels with preeclampsia. Keywords: creatinine clearance, normotensive, preeclampsia.   Abstrak Tujuan: Menentukan hubungan antara creatinine clearance dengan kejadian preeklamsia. Metode: Penelitian potong lintang. Hasil:Dilakukan pemeriksaan creatinine clearance pada 60 sampel ibuhamil > 20 minggu, 30 sampel darah normal dan 30 sampel preeklamsia. Data yang diperoleh dianalisa dengan menggunakan software SPSS versi 22.0 dan dibahas dengan menggunakan  teori literatur yang ada. Kadar rerata creatinine clearance pada kehamilan normotensi 124,650 ± 14,3699 ml / menit / 1,73m2 dan preeklampsia 74,003 ± 23,169 ml / menit / 1,73m2. Setelah uji statistik Mann-Whitney diperoleh nilai p = 0,000. Dari analisis kurva ROC untuk creatinine clearance diperoleh nilai sensitivitas 100% dan spesifisitas 99,53%. Kesimpulan: Ada hubungan yang signifikan  antara creatinine clearance dengan kejadian preeklamsia. Kata kunci: creatinine clearance, normotensi, preeklampsia.